“Containership Markets”: A Comparison with Bulk Shipping and a Proposed Oligopoly Model - Goulielmos , Alexander M. (SPOUDAI Journal of Economics and Business, 2017)
The paper unveils the market structure of container shipping, which suffers by many interpretations. Existing models regress between contestability, duopoly, monopolistic competition and game theory. This paper proposes an oligopoly model with two groups of companies: oligopolists and price-takers. The Lerner’s index found equal to 0.16 excluding perfect competition for the industry; 0.46 and 0.38 found for the most successful carrier the Hyundai. We argue that carriers adjust rates in negotiation with big shippers based on an estimation of supply and demand for the year to come. Negotiations cover: a tentative emergency fee; the level of the quality of service and the bunker surcharge. In all other aspects, container shipping tends to resemble bulk shipping: exhibiting cycles, recessions/depressions (2002, 2009), excess ordering, and elimination of any ordering of new ships during slumps; also costly order-cancellations, low steaming, scrapping, and lay-ups. High concentration (using HHI and CRn indices) measured in 4 carriers and found 0.315>0.2 in turnover in 2002, indicating oligopoly. The end-2008 the crisis increased concentration. In the 8-top-portsrange, for 10 carriers, HHI varied from 1,767 to 2,399 (2006). In 27-top-ports-range, HHI was 1,880 for KKK, 1,831 for Hanjin and 1,767 for Maersk (2006). For alliances HHI = 1,830 (2006) (CKHY). Seven carriers, who invested in ports (2005), had an overwhelming concentration: HHI varied from 3,035 to 6,746. Concentration helped, however, to improve companies’ revenue (R=0.79). JEL Classification: D21-22, L13, L91.